Understanding of leadership style and organizational culture to improve volunteer’s performance at sini aku bantu community - Pratama, Singgih Eka; Pratama, Andika Putra (Journal of Business and Management, 2020)
Abstract. The success of a Non-Government Organization in achieving its goals, cannot be separated from the important role of volunteers that are in it. As time has evolved and competition is inevitable, preparing volunteers to have a high level of work is a must, which can be proven by the results of the volunteer's performance. It is very important for us to know what factors can improve a volunteer’s performance in a company or organization. In this study, the authors assume that a leadership style and also Organizational Culture can have a good impact on volunteer’s performance. Therefore, to prove it, the authors tries to conduct research on leadership style and organizational culture in the Sini Aku Bantu community to improve the performance of volunteers by using the MLQ (Multifactor Leadership Questionnaire) tools to find out the leadership style that is implemented and also the OCAI (Organizational Culture ssessment Instrument) to know the culture that exists and also the expected culture. The purpose of this research is to provide a suggestion or recommendation to the Sini Aku Bantu Community specifically and also to voluntary Non-Government Organizations to be able to have a picture of the leadership style and organizational culture that might be applied to improve the performance of volunteers, who serve without are paid. The methodology in this study uses a quantitative method by distributing questionnaires to 28 members of the Sini Aku Bantu community Assist Batch 4 2020, which consists of Vice Chairman, Secretary, Project Manager and also member. Questionnaires from each tool provide several questions related to conditions that occur in the community.Keywords: Volunteer Performance, Non-Government Organization, Multifactor Leadership Questionnaire, Organizational Culture Assessment Instrument